Advanced Materials Management in Engineering Projects: A Review of Strategies for Cost and Efficiency Optimization - Behboudi, Soheil; Karimian, Koroosh (Management Strategies and Engineering Sciences, 2022)
Materials management plays a pivotal role in engineering projects, directly influencing cost efficiency and overall project success. This narrative review explores advanced strategies for optimizing cost and efficiency in materials management, with a focus on strategic sourcing, inventory management, and the integration of cutting-edge technologies such as IoT, RFID, and Blockchain. Additionally, the review examines lean management practices and sustainability considerations, highlighting their role in enhancing efficiency while minimizing environmental impact. Through a detailed analysis of existing literature and real-world case studies, the review identifies best practices and outlines practical implications for engineering project managers. The findings underscore the necessity of adopting these strategies to achieve cost-effective and efficient materials management in an increasingly complex project environment.